2002
DOI: 10.1038/sj.hdy.6800007
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of bovine species based on AFLP fingerprinting

Abstract: The Bovini species comprise both domestic and wild cattle species. Published phylogenies of this tribe based on mitochondrial DNA contain anomalies, while nuclear sequences show only low variation. We have used amplified fragment length polymorphism (AFLP) fingerprinting in order to detect variation in loci distributed over the nuclear genome. Computer-assisted scoring of electrophoretic fingerprinting patterns yielded 361 markers, which provided sufficient redundancy to suppress stochastic effects of intraspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 33 publications
7
61
0
3
Order By: Relevance
“…Although descriptions of the placenta and placentomes during later gestational stages in the African buffalo have not been reported, it appears that placental morphology in the two buffalo species, S. caffer and B. bubalis, may be more closely related than to that of cattle. This morphological similarity indicates a closer phylogenetic relationship between the two buffalo species, as suggested by craniological and recent molecular studies [2] and [3]. The knowledge gained from this study forms a basis for further research in reproduction, including assisted reproductive technologies, in the African buffalo.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Although descriptions of the placenta and placentomes during later gestational stages in the African buffalo have not been reported, it appears that placental morphology in the two buffalo species, S. caffer and B. bubalis, may be more closely related than to that of cattle. This morphological similarity indicates a closer phylogenetic relationship between the two buffalo species, as suggested by craniological and recent molecular studies [2] and [3]. The knowledge gained from this study forms a basis for further research in reproduction, including assisted reproductive technologies, in the African buffalo.…”
supporting
confidence: 72%
“…Morphological and molecular studies demonstrate a closer relationship between the two buffalo genera than buffalo to cattle [2] and [3]. Differences in reproductive physiology between these three bovids are reflected most obviously by the differing mean gestation lengths, being 343 days in S. caffer [4], 315 days in B. bubalis and 280 days in B. taurus [1].…”
Section: Introductionmentioning
confidence: 99%
“…These distance measures are best suited for AFLPs as they take account of the sharing of presence alleles but are not affected by the sharing of absent or zero alleles, which are more likely to be homoplasious. PhylTools (Buntjer et al, 2002) was used to generate Nei-Li and Jaccard distance matrices for each of the 1000 bootstrapped datasets, and a consensus neighbour-joining (NJ) tree generated using the NEIGHBOR and CONSENSE modules in PHYLIP (Felsenstein, 1989). For the bootstraps, starting trees for each replicate were obtained by randomizing the input order of the species.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in AFLP patterns correspond to point mutations in or near restriction sites or to insertions and deletions. Depending on the degree of relatedness, AFLP patterns generated by a single primer combination are as informative as the typing of 10-30 SNPs or other bi-allelic markers with negligible effect of co-migration of nonhomologous fragments (Buntjer et al, 2002). AFLP markers have a less dynamic mode of evolution than microsatellites, but still clearly reveal genetic variation.…”
Section: Ij Nijman Et Almentioning
confidence: 99%
“…Mitochondrial DNA (mtDNA) markers reveal introgression via the maternal lineage (Loftus et al, 1994a;Ward et al, 1999;Verkaar et al, 2003). The species origin of the nuclear genome can be inferred from species-specific microsatellite alleles (Frisch et al, 1997;MacHugh et al, 1997), AFLP patterns (Vos et al, 1995;Savelkoul et al, 1999;Buntjer et al, 2002) or mutations in satellite DNA. Previously, we showed that satellite fragment length polymorphism (SFLP), as well as amplified fragment length polymorphisms (AFLP) correlated with introgression of zebu (Bos indicus) in African cattle populations (Nijman et al, 1999).…”
Section: Introductionmentioning
confidence: 99%